The limits to growth — Malthus revived - Detlev Karsten (Intereconomics, 1972)
The publication of “The Limits to Growth — A Report for the Club of Rome's Project on the Predicament of Mankind” has resulted in a world-wide discussion of this vital issue. The following article reviews different aspects of the study.
Keywords: 330; Economic Growth